A Rare Case of Chronic Appendicitis Superimposed on an Incarcerated de Garengeot Hernia Prospectively Identified on Computed Tomography. (20th June 2018) - Goldbach, Alyssa; Hota, Partha; Czulewicz, Andrew; Burgert-Lon, Christine; Agosto, Omar
Abstract : The de Garengeot hernia is an uncommon and potentially confounding pathologic process in which the appendix is contained within a femoral hernia. While typically a benign incidental finding, superimposed acute appendicitis is a rare but serious complication. Identification of this entity is crucial to patient management and ultimately outcome with imaging playing a critical role. Cross-sectional imaging, with either CT or MRI, should be performed in all cases of suspected incarcerated de Garengeot hernia to facilitate the appropriate diagnosis and surgical intervention. Herein, we present the fifth case of a prospective CT diagnosis of the de Garengeot hernia in a 61-year-old female who presented with an irreducible right femoral hernia. The patient underwent CT examination which demonstrated the appendix within the femoral hernia sac with an associated periappendiceal fluid collection. The patient was taken for emergent surgical intervention at which time the appendix was found within the hernia sac. The appendix was removed, the defect repaired, and ultimately the patient recovered well.